Crimean-Congo hemorrhagic fever infections reported by ProMED - Yavuz Ince; Cagla Yasa; Mert Metin; Melda Sonmez; Ece Meram; Barlas Benkli; Onder Ergonul (International Journal of Infectious Diseases, 2014)
Objective: There are limited sources describing the global burden of emerging diseases. We reviewed the Crimean-Congo hemorrhagic fever virus (CCHFV) infections reported by ProMED and assessed the reliability of the data retrieved compared to published reports. We evaluated the effectiveness of ProMED as a source of epidemiological data by focusing on CCHFV infections. Methods: Using the keywords “Crimean Congo hemorrhagic fever” and “Crimean Congo” in the ProMED search engine, we reviewed all the information about the news and harvested data using a structured form, including year, country, gender, occupation, the number of infected individuals, and the number of fatal cases. Results: We identified 383 entries reported between January 1998 and October 2013. A total 3426 infected cases were reported, with 451 fatal cases, giving an overall case fatality rate (CFR) of 13%. Out of 144 cases for which the gender was reported, 97 (67%) were male. Most of the cases were reported from Turkey, followed by Russia, Iran, Pakistan, and Afghanistan. Conclusions: Case reporting systems such as ProMED are useful to gather information and synthesize knowledge on the emerging infections. Although certain areas need to be improved, ProMED provided good information about Crimean-Congo hemorrhagic fever.